Synthesis of key intermediate for (+)-tofacitinib through CoIII(salen)-catalyzed two stereocentered hydrolytic kinetic resolution of (Â±)-methyl-3-(oxiran-2-yl)butanoate - Kamble, Rohit B. (Synthetic Communications, 2018)
An enantiopure piperidine, a key intermediate for the synthesis of (+)-tofacitinib, has been achieved in high optical purity (98% ee) from readily available crotyl alcohol. The key steps involved is a CoIII(salen)-OAc-catalyzed two stereocentered hydrolytic kinetic resolution of (±)-methyl-3-(oxiran-2-yl)butanoate.
Keywords: enantioselective; Hydrolytic kinetic resolution; iodolactonization; γ-Butyralactone